Is Laser Surgery with Balloon Dilatation Treatment Effective in Subglottic Stenosis Developing After Covid-19 Infection? - Akyiğit, Abdulvahap; Eroğlu, Orkun; Kaygusuz, Irfan; Lımoncuoglu, Derda; Demırel, Ismail; Karlıdag, Turgut (My University, 2024)
COVID-19 pneumonia has increased tracheal complications because it increases the need for mechanical ventilation and causes mucosal damage in the airway mucosa. One of these complications is subglottic stenosis. Four patients who developed subglottic stenosis following the COVID-19 infection were examined and referred to the ear, nose, and throat clinic between June 2020 and June 2022. All the patients included in our study were male and 57,75± 14.38 years old on average. The median intubation time was 15.75±7.8 days. All patients received laser surgery with balloon dilatation treatment. The median number of laser surgery with balloon dilatation treatments was 2.25±0.95. We used laser surgery and balloon dilatation as an effective and safe treatment method in our patients to treat subglottic stenosis resulting from the damage caused by COVID-19 pneumonia in the airway mucosa.
Keywords: Covid-19; Balloon Dilatation; Laser; Subglottic Stenosis